2005
DOI: 10.1111/j.1365-2621.2005.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 1‐methylcyclopropene treatment on the shelf life and quality of cherry tomato (Lycopersicon esculentum var. cerasiforme) fruit

Abstract: The use of 1-methylcyclopropene (1-MCP) to extend the shelf life of cherry tomato (Lycopersicon esculentum var. cerasiforme) was investigated. Higher concentrations of 1-MCP delayed the ethylene induced climacteric peaks in mature green (MG) and breaker (BR) fruits. Thirteen days after treatment, control fruits were 55% as firm as fruit treated with 0.11 lL L )1 1-MCP. The initiation of fruit softening, chlorophyll degradation and accumulation of lycopene and carotenoids was delayed in treated fruits. Higher 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 18 publications
8
58
1
4
Order By: Relevance
“…Lycopene was analysed according to the method described by Davis (1976) and Opiyo & Ying (2005). For extracting lycopene, 1 g of homogenised fresh or dried tomato sample was weighed and covered with aluminum foil to exclude light.…”
Section: Lycopenementioning
confidence: 99%
“…Lycopene was analysed according to the method described by Davis (1976) and Opiyo & Ying (2005). For extracting lycopene, 1 g of homogenised fresh or dried tomato sample was weighed and covered with aluminum foil to exclude light.…”
Section: Lycopenementioning
confidence: 99%
“…It was reported that 1-MCP reduced production of ethylene, cell respiration, restrained fruit colour changes, softening, taste and aroma degradation as well as diseases of fruits (Moretti et al, 2002;Wills and Ku, 2002;Mostofi et al, 2003). There are reports that 1-MCP treatment markedly affects also ripening of tomato fruits by inhibiting ethylene production (Opiyo and Ying, 2005;Beno-Moualem et al, 2004;Tassoni et al, 2006;Watkins, 2006;Tadesse et al, 2012), significantly reduces respiration rates in the fruits (Guillén et al, 2007), delays change of fruits colour and reduces softening and decay of stored fruits (Guillén et al, 2006). Between 1-MCP treated and untreated ripe tomato fruits no differences in titratable acidity, soluble solids, fructose and glucose contents were reported (Opiyo and Ying, 2005;Ergun et al, 2006;Guillén et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that 1-MCP treatment markedly affects also ripening of tomato fruits by inhibiting ethylene production (Opiyo and Ying, 2005;Beno-Moualem et al, 2004;Tassoni et al, 2006;Watkins, 2006;Tadesse et al, 2012), significantly reduces respiration rates in the fruits (Guillén et al, 2007), delays change of fruits colour and reduces softening and decay of stored fruits (Guillén et al, 2006). Between 1-MCP treated and untreated ripe tomato fruits no differences in titratable acidity, soluble solids, fructose and glucose contents were reported (Opiyo and Ying, 2005;Ergun et al, 2006;Guillén et al, 2006). Some authors pointed out possibilities of use of the treatment for prolonging shelf life of tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…It improves the skin strength making the cell wall and tissues more resistant and less accessible to the enzymes that are produced by fungi and bacteria, limiting infection while controlling ripening, softening, storage breakdown, rotting and decay at the same time (Hong et al, 1999) An increase in the storage life and improvement of tomato fruit quality is really desirable and the initial step required for ensuring successful marketing is to harvest the crop at the optimum stage of maturity. Full red, vine-ripened tomatoes may be ideal to meet the needs of a roadside stand, but totally wrong if the fruits are destined for long distance shipment (Opiyo et al, 2005). Extending the shelf life of tomatoes is very important for domestic and export markets.…”
Section: Introductionmentioning
confidence: 99%